Students and staff in Makyong Cirle(Simac)- a collaborative University- Community Programme in reviving the dying arts. - Farok Zakaria (2012)
Makyong used to be one of the most popular classical performing Arts in Kelantan in the 50’s, 60’s and 70’s. This art genre was once a star is the 50’s and 60’s. However, recently, it has gone through a stalemate situation and seemed like dying. Siti Zainon Ismail(1985) observed that the dying of Makyong is due to the lack of appreciation and understanding of the local youth towards Makyong. The community project of another dying art that is the the Rebana Kercing of Kampung Laut has proven to be successful in sustaining its popularity and existence in Kelantanese community.